Homozygous Co-Deletion of Type I Interferons and CDKN2A Genes in Thoracic Cancers: Potential Consequences for Therapy - Grard, Marion; Chatelain, Camille; Delaunay, Tiphaine; Pons-Tostivint, Elvire; Bennouna, Jaafar; Fonteneau, Jean-François (Frontiers in Oncology, 2021)
Homozygous deletion (HD) of the tumor suppressor gene CDKN2A is the most frequent genetic alterations in malignant pleural mesothelioma and is also frequent in non-small cell lung cancers. These HD are often accompanied by the HD of the type I interferons (IFN I) genes that are located closed to the CDKN2A gene on the p21.3 region of chromosome 9. IFN I genes encode sixteen cytokines (IFN-alpha, IFN-beta…) that are implicated in cellular antiviral and antitumor defense and in the induction of the immune response. In this review, we discuss the influence of IFN I genes HD on therapy of thoracic cancers and speak in favor of a better taking into account of these HD in monitoring of patients.